Use of Biowaste for Sodium Removal in Mediterranean Irrigation Water: A Sustainable Approach - Dámaris Núñez-Gómez; Alejandro Andy Maciá-Vázquez; Carlos Giménez-Valero; Juan José Martínez-Nicolás; Pilar Legua; Pablo Melgarejo (Clean Technologies)
The Mediterranean region faces significant water scarcity, a challenge intensified by climate change, impacting both agricultural productivity and water quality. High sodium levels in irrigation water compromise soil structure, leading to reduced crop yields and economic strain. This study investigates the use of sustainable adsorbents derived from agricultural residues (almond shell, eggshell, and pumice) for the removal of sodium from irrigation water. These materials, widely available in the Mediterranean, support circular economy principles by repurposing biowaste to address agricultural challenges. Adsorption experiments were conducted using real irrigation water, capturing the complexity of its physicochemical properties to evaluate the effectiveness of these biosorbents under practical conditions. A Central Composite Rotational Design (CCRD) was applied to optimize adsorption parameters, focusing on adsorbent concentration, agitation, and contact time. Kinetic studies indicated that sodium adsorption adhered to a pseudo-second order model, suggesting a chemically controlled process. Isotherm analysis, with a strong fit to the Jovanovic model, confirmed a predominantly monomolecular adsorption mechanism across all adsorbents, while the Freundlich model highlighted site heterogeneity. Microscopy and energy-dispersive X-ray spectroscopy (EDX) revealed structural modifications in the adsorbents before and after treatment. The porous internal structure of the almond shell displayed significant sodium retention, while the calcified eggshell surface showed high initial adsorption efficiency but rapid site saturation. Pumice, noted for its extensive porosity, sustained adsorption capacity even with surface deposits formed during treatment. This research demonstrates the potential of biowaste-derived adsorbents for efficient sodium removal from complex aqueous systems, offering a viable solution for sustainable agriculture and improved soil and water management in Mediterranean regions.